The Stability of Metallic MoS(2) Nanosheets and Their Property Change by Annealing - Li, Li (Nanomaterials (Basel), 2019)
Highly pure 1T MoS(2) nanosheets were grown at 200 °C by a hydrothermal process. The effects of mild annealing on the structural and physical properties of the MoS(2) were studied by heating the nanosheets in air and vacuum up to 350 °C. It was found that the annealing leads to an increase in resistivity for the nanosheets by 3 orders of magnitude, the appearance of two absorption bands in the visible range, and a hydrophilic to hydrophobic change in the surface wetting properties. Monitoring of the annealing process by Raman spectroscopy indicates that the material property changes are associated with a 1T to 2H MoS(2) phase transition, with activation energies of 517 meV in air and 260 meV in vacuum. This study provides another way to control the electrical, optical, and surface properties of MoS(2) nanosheets for fulfilling the needs of various applications.